Category Selectivity of Human Visual Cortex in Perception of Rubin Face–Vase Illusion - Wang, Xiaogang; Sang, Na; Hao, Lei; Zhang, Yong; Bi, Taiyong; Qiu, Jiang (Frontiers in Psychology, 2017)
Bistable perception, Rubin face-vase illusion, task-related fMRI, multivariate pattern analysis, fusiform face area